Thermo-mechanical and material flow characteristics of tool sequencing dynamics in refill FSSW of thin alclad AA7075-T6 sheets: Numerical analysis using meshless smoothed-particle hydrodynamics method - Venkata Somi Reddy Janga; Mokhtar Awang; Nabihah Sallih; Tamiru Alemu Lemma (Journal of Advanced Joining Processes)
This study is focused on improving the joint strength of AA7075-T6 specimens with aluminium cladding (alclad) joined through the refill friction stir spot welding (RFSSW) process. The bonding ligament weakens the RFSSW joint because the alclad layer is trapped between the specimens. This layer hinders material mixing during welding and creates a weak interface prone to crack initiation and propagation during external loading, affecting joint integrity. To overcome this problem, a novel tool sequencing variant of RFSSW, the pin plunging reinforced RFSSW (PPRSP-RFSSW), is proposed. A smoothed-particle hydrodynamics (SPH) formulation-based 3D thermo-mechanical model is developed to study the thermo-mechanical and material flow properties as it is possible to trace the field variables explicitly; it can manage significant material/elemental deformations and capture material mixing dynamically. The PPRSP-RFSSW is numerically analyzed and compared to existing sleeve plunging RFSSW (SP-RFSSW). The numerical model's accuracy was tested by comparing temperatures to experimental temperature data in published papers, and the results corresponded well. Comparisons are made between the SP-RFSSW and PPRSP-RFSSW concerning their heat distribution, plasticization, and material flow. Enhanced material mixing and plasticization were observed through PPRSP-RFSSW, and this tool sequencing is recommended for joining alclad AA7075-T6 specimens.